PSIKOSIS PADA AUTOIMUN SEBUAH LAPORAN KASUS SISTEMIK LUPUS ERITEMATOSUS KOINSIDENSI DENGAN MULTIPLE SKLEROSIS - Deshinta Putri Mulya; Arief Darmawan (Collaborative Medical Journal, 2022)
Varied symptoms of Systemic lupus erythematosus make its diagnosis challenging. A 40 year old woman was admitted to the Emergency Room for self-talking, rambling and being rowdy. Psychiatric assessment showed an indication of organic hallucination. The patient had been undergoing neurologic treatment for four months due to multiple sclerosis with onset symptoms including of paraperese which was improved after taking steroids. In addition to neurologic symptoms, other conditions including mucous ulcers, malar rash, vasculitis, hair loss, and arthritis were found. The laboratory test indicated the presence of strong positive ANA profile in the RNP/Sm, Sm, SS-A native, Ro-52, SS-B and Ribosomal Protein. Patient’s condition significantly improved after undergoing treatment for Systemic lupus erythematosus flare with a coincidence of multiple sclerosis.